Value orientations of modern teenagers (Actual Problems of Psychology in Educational Institutions, 2018)
The concept of value orientations is characterized in the article,the main factors of their formation are systematized. The analysis of thetheoretical foundations of the problem of value orientations became the basis forsubstantiating the psychological structure of value orientation. Psychologicalcharacteristics of the formation of values were defined. It was determined whatvalue orientations prevail in modern adolescents: health, the presence of goodand faithful friends, an active, active life, a happy family life. The realization ofthe potential of the individual occurs only with the support of value orientations.The gender aspect of values is presented. The ways of effective formation ofvalue orientations in adolescence are revealed in different social situations:family, school, age, teacher, media.
Keywords: value orientations, values, personality, adolescents, gender